EKONOMI KREATIF SEBAGAI LOKOMOTIF BARU PEREKONOMIAN INDONESIA MENUJU INDONESIA YANG MAJU - Firdaus, Azka Rifqi; Vynatria, Anggun Devaga; Husna, Siti Lulu'ul; Alfareza, M. Fian Nur; Hidayah, Asmi Ayuning (Yayasan Pendidikan Penelitian Pengabdian Algero, 2024)
In recent years, attention towards the creative economy has increased on a global scale. This concept refers to an economy that is not only based on physical goods, but also involves the ownership of intangible assets, such as innovation and creativity. This article aims to explain how the creative economy can become a major driver in Indonesia's economy, potentially leading the country towards a more advanced future. The discussion includes a paradigm shift from an economy focused on physical production to one that emphasizes innovation, as well as a transformation from a recorded economy to a creativity-based economy. Furthermore, the article reveals how the creative economy can help Indonesia develop more innovative industries and compete in the international market. The use of the creative economy is also expected to reduce poverty levels and create a brighter future for the national economy. Therefore, success in implementing policies and utilizing Indonesia's high creative potential will lead the country towards an innovative, competitive, and sustainable economy in the future.